Strategi Kampanye Humas BMKG dalam Memberikan Peringatan Dini Hidro Meteorologi pada Masyarakat melalui Akun Instagram @ppid_bmkg - Tegar Nurrahman; Murtiadi; Roynaldi Arista (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
The Meteorology, Climatology, and Geophysics Agency is one of the Non-Departmental Government Institutions (LPND). BMKG has offices spread throughout Indonesia, and is centered in Kemayoran, Jakarta. This study aims to describe the public relations campaign strategy implemented by BMKG Public Relations in providing hydrometeorological early warnings to the public through Instagram media @PPID_BMKG. This study uses a qualitative research method. Data collection techniques are carried out by means of observation, interviews, and documentation. The results of the study show that BMKG's public relations campaign strategy is based on the approach proposed by Cutlip, Center, & Broom. This campaign strategy is carried out through several stages including systematic content planning, using easy-to-understand visual language, and measuring effectiveness using social media insight analysis and making monthly reports every three months. This study emphasizes the importance of cooperation between BMKG and social media to increase public awareness and preparedness in facing hydrometeorological disasters.